Answer:
the answer is 96°
Step-by-step explanation:
it is an isosceles triangle as it's 2 sides are equal.
for an isosceles triangle, the angles made by the equal sides with the third side are equal.
and the sum of all angles in a triangle = 180°
42 + 42 + x = 180
x = 180 - 84
X = 96°
Answer:
Option D) F
Step-by-step explanation:
we have
-----> inequality A
The solution of the inequality A is the shaded area below the dashed line ![y=-2x+10](https://tex.z-dn.net/?f=y%3D-2x%2B10)
The y-intercept of the dashed line is (0,10)
The x-intercept of the dashed line is (5,0)
----> inequality B
The solution of the inequality B is the shaded area below the dashed line ![y=\frac{1}{2}x-2](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B1%7D%7B2%7Dx-2)
The y-intercept of the dashed line is (0,-2)
The x-intercept of the dashed line is (4,0)
The solution of the system of inequalities is the shaded area between the two dashed lines
see that attached figure
Remember that
If a ordered pair is a solution of the system of inequalities, then the ordered pair must lie on the shaded area of the solution
therefore
The solution are the points
E, F and G
Answer:
14$ per sweater
Step-by-step explanation:
264 - 96 = 168
168 / 12 = 14
Answer:
The given fraction
reduces to ![\frac{x-1}{x}](https://tex.z-dn.net/?f=%5Cfrac%7Bx-1%7D%7Bx%7D)
Step-by-step explanation:
Consider the given fraction ![\frac{x^3-x^2}{x^3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E3-x%5E2%7D%7Bx%5E3%7D)
We have to reduce the fraction to the lowest terms.
Consider numerator ![x^3-x^2](https://tex.z-dn.net/?f=x%5E3-x%5E2)
We can take x² common from both the term,
Thus, numerator can be written as
Given expression can be rewritten as ,
![\frac{x^3-x^2}{x^3}=\frac{x^2(x-1)}{x^3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E3-x%5E2%7D%7Bx%5E3%7D%3D%5Cfrac%7Bx%5E2%28x-1%29%7D%7Bx%5E3%7D)
We can now cancel
from both numerator and denominator,
![\Rightarrow \frac{x^2(x-1)}{x^3}=\frac{x^2(x-1)}{x^2 \cdot x}](https://tex.z-dn.net/?f=%5CRightarrow%20%5Cfrac%7Bx%5E2%28x-1%29%7D%7Bx%5E3%7D%3D%5Cfrac%7Bx%5E2%28x-1%29%7D%7Bx%5E2%20%5Ccdot%20x%7D)
![\Rightarrow \frac{(x-1)}{x^2 \cdot x}=\frac{x-1}{x}](https://tex.z-dn.net/?f=%5CRightarrow%20%5Cfrac%7B%28x-1%29%7D%7Bx%5E2%20%5Ccdot%20x%7D%3D%5Cfrac%7Bx-1%7D%7Bx%7D)
Thus, the given fraction
reduces to ![\frac{x-1}{x}](https://tex.z-dn.net/?f=%5Cfrac%7Bx-1%7D%7Bx%7D)